2018
DOI: 10.1111/bjhp.12299
|View full text |Cite
|
Sign up to set email alerts
|

‘It's a silver lining’: A template analysis of satisfaction and quality of life following post‐mastectomy breast reconstruction

Abstract: This study provides new insights into post-mastectomy breast reconstruction and is a novel application of template analysis. The analysis demonstrates only slight variation in some categories of experience among women, despite a heterogeneous sample. The findings allow researchers and clinicians to focus on specific dimensions of satisfaction and quality of life to support the needs of women following reconstruction. Statement of contribution What is already known on this subject? Patient satisfaction and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…Santosa et al, found that psychosocial, physical, and sexual well‐being increased with time after this surgery. However, Matthews and colleagues did not find this variable to be a significant predictor of quality of life.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Santosa et al, found that psychosocial, physical, and sexual well‐being increased with time after this surgery. However, Matthews and colleagues did not find this variable to be a significant predictor of quality of life.…”
Section: Resultsmentioning
confidence: 94%
“…Two studies suggested that older patients reported higher levels of overall quality of life after breast reconstruction . The remaining studies did not report significant differences between younger and older patients …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations